Narrow band imaging in the diagnosis of bladder schistosomiasis. Issue 4 (7th April 2020) - Jimie, Joachim; Lyttle, Margaret
Abstract : A 23-year-old man presented to us with multiple episodes of visible haematuria associated with dysuria, but no other symptoms suggestive of infection. His physical examination was completely unremarkable. On detailed evaluation of history, it was noted that he was treated for urinary schistosomiasis as a child in Sudan. A diagnostic flexible cystoscopy, with both white light and narrow band imaging (NBI), was done among other tests as a further diagnostic tool to investigate possible causes. This revealed the characteristic features of bladder schistosomiasis. Urine microscopy for S chistosoma haematobium eggs was negative, and this could have caused the diagnosis to be missed. He was treated with praziquantel for chronic bladder schistosomiasis. This is the first time that the use of NBI as an adjunct to white light imaging in the diagnosis of bladder schistosomiasis has been reported.